Musculoskeletal sarcoidosis: A single center experience over 15 years. (9th February 2021) - Patil, Sanjeev; Hilliard, Carolyn A.; Arakane, Masumi; Koppisetti Jenigiri, Sreedevi; Field, Elizabeth H.; Singh, Namrata
Abstract: Background: Musculoskeletal (MSK) sarcoidosis presents with a variety of clinical phenotypes. Four subtypes of MSK sarcoidosis have been identified to date: Lofgren syndrome, chronic sarcoid arthritis, osseous sarcoidosis, sarcoid myopathy. Each subtype has been reported with varying incidence mainly due to lack of universal classification criteria. Methods: We performed a retrospective chart review of patients with MSK sarcoidosis at a single academic center between January 2000 and December 2014. Descriptive statistics were used to describe the proportion of patients with sarcoidosis who had the 4 MSK syndromes of interest, demographic characteristics and therapeutic agents used. Results: A cohort of 58 patients with MSK manifestations were identified among 1016 patients with sarcoidosis. Frequency of subtypes include: Lofgren syndrome 46.6%, osseous sarcoidosis 25.9%, chronic sarcoid arthritis 24.1% and sarcoid myopathy 6.9%. The cohort was predominantly female (43/58 patients, 74%) and Caucasian (48/58 patients, 82.8%). Mean age was 47.2 years. One patient had overlap of osseous sarcoidosis and chronic sarcoid arthritis, another patient initially had Lofgren syndrome and later developed chronic sarcoid arthritis. Sarcoid myopathy patients presented with myalgia more often than muscle weakness. Conclusion: We identified a large cohort of MSK sarcoidosis and determined the prevalence of all 4 subtypes. In patients who do develop MSK manifestations of sarcoidosis, they are commonly a part of the initial presentation of sarcoidosis. There is an unmet need to establish standardized classification criteria for the 4 MSK sarcoidosis syndromes.